Edukasi Perawatan Luka Diabetes Melitus Bagi Keluarga Penderita di Komunitas - Dunggio, Abdul Rivai Saleh; Ibrahim, Ikhsan (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Diabetes Mellitus (DM) is a chronic disease that can lead to serious complications, one of which is diabetic ulcers (diabetic wounds). Diabetic wounds require proper care to prevent infection, amputation, and even death. However, many families of DM patients still lack understanding of how to care for wounds at home. This community service project aims to improve the knowledge and skills of families of DM patients in performing simple wound care in the community. The implementation method included counseling, wound care demonstrations, and family support. The results of the activity showed an increase in family understanding of the principles of diabetic wound care, hygiene, and complication prevention. In conclusion, the education provided effectively improved families' ability to care for diabetic wounds, thereby improving the patient's quality of life.